Carbon-based nanomaterials as scaffolds in bone regeneration. (16th November 2020) - Crisan, Liana; Crisan, Bogdan Vasile; Bran, Simion; Onisor, Florin; Armencea, Gabriel; Vacaras, Sergiu; Lucaciu, Ondine Patricia; Mitre, Ileana; Baciut, Mihaela; Baciut, Grigore; Dinu, Cristian
Abstract: Bone tissue regeneration and mineralization are major challenges in the reconstruction of congenital defects, tumor resections or fractures. The natural bone is comprised of unique architectural design from the nanoscale to macroscale dimensions mainly composed of collagen nano-fibrils and nano-hydroxyapatite. Recent advances in stem cell research and nanotechnology have significantly influenced the landscape of tissue engineering with applications in bone regeneration. Carbon-based nanomaterials have been attracting increasing attention in the field of biology and biomedicine. The discovery of graphene marks the beginning of a new era in material sciences research. Graphene introduction in tissue engineering offered unique scaffold structures with exceptional mechanical and electrical properties. It is a versatile carbon-based structure that serves as a potential backbone for multi-component nanostructural biomimetic scaffolds, designed to have a morphological and chemical structure for integration with bone. Graphene and its chemical derivatives have the potential to promote cell adhesion, proliferation, and differentiation. Also, we will present considerations about osteogenesis through tissue engineering. In particular, we will discuss the biocompatibility of the osteoprogenitors cells with composite materials obtained through nanotechnological processes.